La “Gran Historia” (Big History) y el Antropoceno: dos nuevos enfoques del pasado y el presente - Udías Vallina, SJ, Agustín (Razón y fe, 2019)
Big History is a recent approach that presents a unitary view of history from the big-bang to the present day, proposed by Australian historian David Christian in 1991 and developed in his books. It presents, therefore, the formation of the first atoms, that of the stars and of the planet Earth around one of them, the evolution of life on Earth, the appearance of man and his evolution to reach the present. The last epoch, with the interaction of man on the surface of the Earth itself modifying it, today receives the name of Anthropocene (the last 200 years). On the Big History idea is based the Higher-ed and secondary school educational project «Big History Project», which is already established in many parts of the world. Relationships between the Great History and the thought of Teilhard de Chardin can be appreciated.
Keywords: Big History; David Christian; Biosphere; Noosphere; Anthropocene; Big History Project; Teilhard de Chardin